2010
DOI: 10.1007/s10600-010-9627-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective oxidation of oleanolic acid derivatives with ozone

Abstract: Oleanolic acid (1) belongs to a class of pentacyclic triterpenoids that is observed in >120 plants of various species (e.g., ginseng, apple and olive skin, calendulum and silphium flowerheads, white mistletoe, etc.[1]). It is responsible for several valuable medicinal properties of their extracts. Oleanolic acid and its derivatives exhibit a broad spectrum of pharmacological activity including hepatoprotective, anti-inflammatory, antimicrobial, antiviral, antitumor, etc. [2, 3]. Oleanolic acid is approved for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We recently showed that oxidation of oleanolic acid methyl ester with an excess of ozone produced 3,12-dioxoolean-28-oic acid [7]. Oxidation of 11-deoxoglycyrrhetic acid occurred analogously to form the 3,12-diketone [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that oxidation of oleanolic acid methyl ester with an excess of ozone produced 3,12-dioxoolean-28-oic acid [7]. Oxidation of 11-deoxoglycyrrhetic acid occurred analogously to form the 3,12-diketone [5].…”
mentioning
confidence: 99%
“…Moreover, the C-3 hydroxyl of ursolic acid methyl ester (5) was stable to the action of ozone, in contrast with oleanolic and 11-deoxoglycyrrhetic acids [5,7]. The reaction produced 3E-hydroxyoxetane 6.…”
mentioning
confidence: 99%
“…We found earlier that oleanolic acid methyl ester was oxidized by ozone to methyl 12-oxoolean-28-oate [23] whereas oxidation of the analogous ursolic acid derivative gave 12-oxo-11S,13R-oxetane on ring C [24]. Limitations of methods for synthesizing such chiral non-racemic oxetanes were noted [25].Considering the aforementioned examples and continuing research on oxidative transformations of plant terpenoids [11,12,14,17,18,[26][27][28], we decided to determine the direction of the oxidation by ozone of 2-cyano-3,4-seco-4(23)-ene ursolic acid methyl ester (1) and to compare the results with those published for oxidation of the analogous oleanolic acid derivative [23].Oxidation of 1 with two unsaturated bonds in the C-4(23) (ring A) and C-12(13) (ring C) positions by ozone in CH 2 Cl 2 formed the three 2-cyano-3,4-seco-4-oxo derivatives 12-oxours-11S,13R-oxetane (2, 68%), 11-oxours-12-ene (3, 12%), and 12-hydroxy-4,11-dioxours-12-ene (4, 8%) (Scheme 1). Thus, oxidation of methyl 2-cyano-3,4-seco-4(23)-ene ursolate by ozone was non-selective, in contrast with the oxidation of the analogous oleanolic acid derivative, which enabled selective transformations of rings A and C to be carried out [23].…”
mentioning
confidence: 99%
“…Considering the aforementioned examples and continuing research on oxidative transformations of plant terpenoids [11,12,14,17,18,[26][27][28], we decided to determine the direction of the oxidation by ozone of 2-cyano-3,4-seco-4(23)-ene ursolic acid methyl ester (1) and to compare the results with those published for oxidation of the analogous oleanolic acid derivative [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation